226k views
0 votes
If f(x)=3x^2-2x+4 and g(x)=5x^2+6x-8,find (f-g) (x)

User HuaTham
by
5.4k points

2 Answers

4 votes

Answer:


- 2( {x}^(2) - 4x + 6)

Explanation:


f(x)=3x^2-2x+4 \\ g(x)=5x^2+6x-8 \\ (f-g) (x) = 3 {x}^(2) - 2x + 4 - (5 {x}^(2) + 6x - 8) \\ = 3 {x}^(2) - 2x + 4 - 5 {x}^(2) - 6x + 8 \\ = - 2 {x}^(2) - 8x + 12 \\ = - 2( {x}^(2) - 4x + 6)

User Natural
by
5.7k points
4 votes

Answer:

-2x^2-8x+12

Explanation:

f(x)=3x^2-2x+4

g(x)=5x^2+6x-8

(f-g) (x)= 3x^2-2x+4 - (5x^2+6x-8)

Distribute the minus sign

(f-g) (x)= 3x^2-2x+4 - 5x^2-6x+8

Combine like terms

=-2x^2-8x+12

User David Bick
by
6.1k points